The early detection of tongue cancer with the etiology of mechanical trauma - Setyawan, Aris; Anang, Zhavira Dwiyanti; Rahmawati, Rizki Nurida; Kumalasari, Winda; Noor, Alfi Dian Uly; Yulianti, Rima Talitha (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Oral squamous cell carcinoma (OSCC) occurs in approximately 95% of people older than 40 years; usually, it is diagnosed at the age of 60 years. The etiology of OSCC is multifactorial. Chronic mechanical trauma due to sharp teeth has also been suggested as an etiology of oral squamous of the tongue. Purpose: This case report aimed to describe the etiology of OSCC resulting from mechanical trauma and to prevent further metastasis by correctly diagnosing the lesion earlier. Case: A 49-year-old female patient presented with painful and swollen stomatitis two months ago. No submandibular lymph nodes were palpable. An indurated ulceration and sharp teeth on the right region of the jaw were obtained from the intraoral examination. Malignancy was concluded from Histopathology Examination (HPE) and Magnetic Resonance Imaging (MRI) radiography results. Case Management: Multiple extractions were chosen to eliminate the etiology of mechanical trauma due to sharp teeth, and the patient underwent hemiglossectomy with the keyhole method. Postoperative, the histopathology examination revealed an OSCC of the tongue. The patient is currently in the second cycle of chemotherapy by hematologist-oncologists. Conclusion: The early appropriate diagnosis of a tongue ulcer can prevent metastasis, decrease morbidity, and increase quality of life.